2021
DOI: 10.3390/ijerph182111171
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the 30-Day and 1-Year Smoking Abstinence of Women in Korea: The Effect of Nicotine Dependency, Self-Efficacy, and Mental Illness

Abstract: Despite the success of tobacco control efforts in reducing smoking rates during the past 50 years, data on the factors contributing to quitting success are still lacking. Smoking-related mortality among women has also not declined. Therefore, this study aimed to characterize sociodemographic features, smoking-related behaviors, mental illness, and smoking cessation in woman smokers in Korea who were registered in the Quitline program. Furthermore, factors associated with 30-day and 1-year successful smoking ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The smokers' PPAR at follow-up at 1 month with low, moderate, and severe nicotine dependence was 33.67%, 32.32%, and 22.18%, respectively. For CAR at 3 months, those with moderate (AOR=0.64; 95% CI: 0.44-0.92) and severe (AOR=0.50; 95% CI: 0.34-0.72) nicotine dependence are more likely to fail than those who have a low nicotine dependence, in alignment with other studies 30,34 . This may be attributed to smokers with moderate to severe nicotine dependence being more likely to suffer from severe withdrawal symptoms and stronger tobacco cravings, hence the higher likelihood of relapse.…”
Section: Discussionsupporting
confidence: 88%
“…The smokers' PPAR at follow-up at 1 month with low, moderate, and severe nicotine dependence was 33.67%, 32.32%, and 22.18%, respectively. For CAR at 3 months, those with moderate (AOR=0.64; 95% CI: 0.44-0.92) and severe (AOR=0.50; 95% CI: 0.34-0.72) nicotine dependence are more likely to fail than those who have a low nicotine dependence, in alignment with other studies 30,34 . This may be attributed to smokers with moderate to severe nicotine dependence being more likely to suffer from severe withdrawal symptoms and stronger tobacco cravings, hence the higher likelihood of relapse.…”
Section: Discussionsupporting
confidence: 88%
“…10 A recent study showed that low nicotine dependence improved the likelihood of quitting smoking at the 30-day and 1-year follow-up in 3360 women smokers using the Korean Quitline program. 24 Another study of 484 subjects showed that low nicotine dependence was associated with a high continuous abstinence rate. 14 A recent study found that a lower FTND score (0-3 points) for measuring nicotine dependence was related to smoking success in 1395 smokers at a smoking cessation program in 12 weeks based on a hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco craving questionnaire (≤ 202, ≥ 203 points). 16 Self-efficacy scores for smoking cessation were divided into tertiles (low [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], middle [25][26][27][28][29][30], and high [31-45]). 17 The drug regimens included NRT, including nicotine patches, lozenges, gum, and prescription drugs (varenicline or bupropion).…”
Section: Risk Factors' Variablesmentioning
confidence: 99%
See 1 more Smart Citation